2010
DOI: 10.1172/jci41004
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic promise of the cancer stem cell concept

Abstract: Cancer stem cells (CSCs) are a subpopulation of tumor cells that selectively possess tumor initiation and self-renewal capacity and the ability to give rise to bulk populations of nontumorigenic cancer cell progeny through differentiation. As we discuss here, they have been prospectively identified in several human malignancies, and their relative abundance in clinical cancer specimens has been correlated with malignant disease progression in human patients. Furthermore, recent findings suggest that clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
486
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(503 citation statements)
references
References 124 publications
11
486
0
2
Order By: Relevance
“…TICs are able to generate the heterogeneous lineages of cancer cells that comprise the tumour, and hence have been advocated to constitute the sustaining force to maintain and renew fully established malignancy. These properties of TICs have therefore led to the proposal that TICs are responsible for tumour occurrence, metastasis and recurrence, and TIC-targeted therapeutic approaches may provide promising strategies to improve clinical cancer therapy 4 .…”
mentioning
confidence: 99%
“…TICs are able to generate the heterogeneous lineages of cancer cells that comprise the tumour, and hence have been advocated to constitute the sustaining force to maintain and renew fully established malignancy. These properties of TICs have therefore led to the proposal that TICs are responsible for tumour occurrence, metastasis and recurrence, and TIC-targeted therapeutic approaches may provide promising strategies to improve clinical cancer therapy 4 .…”
mentioning
confidence: 99%
“…Increasing evidence from hematopoietic malignancies and solid tumors (including brain, breast, colorectal, head and neck cancers) has strongly supported the concept that a subpopulation of cancer cells in each tumor has greater potential of cancer initiation and repopulation (Lapidot et al, 1994;Bonnet and Dick, 1997;Al-Hajj et al, 2003;Hemmati et al, 2003;Singh et al, 2003;Galli et al, 2004;Singh et al, 2004;Ricci-Vitiani et al, 2007;O'Brien et al, 2007;Dalerba et al, 2007;Prince et al, 2007;Schatton et al, 2008). These cells were called cancer stem cells (CSCs) or tumor-initiating or propagating cells because they share some critical characteristics with normal stem cells, including the capacities for self-renewal, multi-lineage differentiation, and maintained proliferation (Reya et al, 2001;Vescovi et al, 2006;Bao et al, 2006a;Rosen and Jordan, 2009;Park and rich, 2009;Heddleston et al, 2010;Frank et al, 2010). Although cancer stem cell or stem cell-like cancer cell terminology is imperfect due to its distinct differences from normal stem cell, but it does capture the shared characteristics with normal stem cells especially somatic stem cells.…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that most solid tumors contain a distinct subpopulation of cancer stem cells (CSCs), which represent the source for tissue renewal, hold malignant potential and can be responsible for therapy resistance [3][4][5][6], and it has been suggested that a successful cure of cancer should requires eradication of CSCs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%